The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3390/rs6065090
|View full text |Cite
|
Sign up to set email alerts
|

A Spectral Decomposition Algorithm for Estimating Chlorophyll-a Concentrations in Lake Taihu, China

Abstract: Abstract:The complex interactions among optically active substances in Case II waters make it difficult to associate the variability in spectral radiance (or reflectance) to any single component. In the present study, we developed a four end-member spectral decomposition model to estimate chlorophyll-a concentrations in a eutrophic shallow lake-Lake Taihu. The new model was constructed by simulated spectral data from Hydrolight and was successfully validated using both of simulated reflectance and in situ refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Therefore, compared to the conventional models, this approach is less sensitive to geographical and temporal variability. If the standard reflectance spectra of the respective endmember remain consistent with similar spectral sensitivity, this model could be applied to other satellite images [51,73]. The new model is capable of estimating the SAV biomass for the whole lake basin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compared to the conventional models, this approach is less sensitive to geographical and temporal variability. If the standard reflectance spectra of the respective endmember remain consistent with similar spectral sensitivity, this model could be applied to other satellite images [51,73]. The new model is capable of estimating the SAV biomass for the whole lake basin.…”
Section: Discussionmentioning
confidence: 99%
“…Through photosynthesis, the phytoplankton converts CO 2 and H 2 O into O 2 and is responsible for primary production in the water column [6,12]. In addition, chl a is the main indicator of phytoplankton biomass [13][14][15] and can be used to determine the water clarity [9]. Phytoplankton blooms are natural processes in the water environment, which show the normal functioning of a water ecosystem [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is specified here that these turbid water indices were tuned using the same data set used for GUC2 formulation ( n = 41). Several studies (Chen & Quan, ; Li et al, ; Zhang et al, , , ) in Asian case II waters, Moses et al () in Azov Sea, Gilerson et al () in Nebraska lakes, Kutser et al () in boreal and arctic lakes with high CDOM load, and Ligi et al () in the Baltic waters are few examples that have demonstrated the applicability of different NIR‐Red band ratio schemes in optically complex waters for the retrieval of CHL . For example, the resulting mean absolute error percentages were more than 100%, and RMSE as much as 32.55 μg/L for CHL ranging up to 30 μg/L (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is specified here that these turbid water indices were tuned using the same data set used for GUC2 formulation (n = 41). Several studies (Chen & Quan, 2013;Li et al, 2011;Zhang et al, 2011Zhang et al, , 2014Zhang et al, , 2015 in Asian case II waters, Moses et al (2009) in Azov Sea, Gilerson et al (2010) in Nebraska lakes, Kutser et al (2016) (Li et al, 2012). The error in estimations is mostly consistent for CHL concentrations less than 10 μg/L while high CHL loads results in relatively decreased mean absolute error percentages, thereby different forms of turbid water algorithms are needed for different ranges, and that too, for specific water types.…”
Section: Performance Of Guc2 Algorithmmentioning
confidence: 99%